2021
DOI: 10.1186/s13613-021-00905-6
|View full text |Cite
|
Sign up to set email alerts
|

Can the cytokine adsorber CytoSorb® help to mitigate cytokine storm and reduce mortality in critically ill patients? A propensity score matching analysis

Abstract: Background A cytokine storm is life threatening for critically ill patients and is mainly caused by sepsis or severe trauma. In combination with supportive therapy, the cytokine adsorber Cytosorb® (CS) is increasingly used for the treatment of cytokine storm. However, it is questionable whether its use is actually beneficial in these patients. Methods Patients with an interleukin-6 (IL-6) > 10,000 pg/ml were retrospectively included between Octo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 35 publications
9
34
0
Order By: Relevance
“…It is also true that IL-6 may not be the optimal parameter for assessing the effectiveness of therapy with CytoSorb, as previously discussed [ 7 ]. This consideration is consistent with observations from another retrospective analysis [ 8 ]. However, this cannot explain the association of cytokine adsorption with mortality in the CYCOV trial.…”
supporting
confidence: 93%
“…It is also true that IL-6 may not be the optimal parameter for assessing the effectiveness of therapy with CytoSorb, as previously discussed [ 7 ]. This consideration is consistent with observations from another retrospective analysis [ 8 ]. However, this cannot explain the association of cytokine adsorption with mortality in the CYCOV trial.…”
supporting
confidence: 93%
“…In vitro studies have demonstrated the optimal capacity for removing broad-spectrum cytokines with removal rates of >90% at 120 min [125]. However, there have been reports that IL-6 did not decrease in clinical cases [127], and the evidence supporting its favorable outcomes on hemodynamic parameters and blood lactate levels has been limited to a case series [128]. Despite such promising experimental results, only a randomized controlled trial has evaluated the efficacy of CytoSorb ® in critically ill patients with sepsis.…”
Section: Cytokine Adsorbing Columnmentioning
confidence: 99%
“…Procalcitonin is equally adsorbed, which must be taken into account in the interpretation of lab test results [ 30 , 32 ]. However, the IL6 concentration, which is frequently used to indicate start and efficacy of hemoadsorption therapy and for the assessment of the effect of hemoadsorption, has recently been questioned for its usefulness since the levels are balanced by the endogenous turn-over and the extracorporeal elimination [ 72 , 73 , 74 ]. CytoSorb ® therapy could be useful in septic shock [ 75 , 76 ], but indication, indication thresholds and duration of therapy are controversially discussed.…”
Section: Hemoadsorption With Cytosorb ®mentioning
confidence: 99%
“…More retrospective studies demonstrated a mortality benefit for hemoadsorption [ 81 ], especially if CytoSorb ® therapy was started early (within 12 h) [ 82 ]. On the other hand, several recently published studies have failed to demonstrate any effect of hemoadsorption on mortality [ 74 , 83 ].…”
Section: Hemoadsorption With Cytosorb ®mentioning
confidence: 99%